Mandatory Testament for heirs of different religions - Ika Prabowo, Laurensia Sherlyn Tania; Wardana, Nyoman Arya Kusuma; Indriarukmana, Amelya Rizky; Prastiyowati, Dian; Oliviantari, Sofia Ramdhani (LEGAL BRIEF, 2024)
A Testament as part of an inheritance is given to heirs or relatives who do not receive a share of the inheritance because they are prevented by religious rules. Problems arise because the Compilation of Islamic Law does not strictly regulate inheritance for heirs of different religions. Article 171 letter c of the Compilation of Islamic Law determines that the heir is someone who is Muslim. However, it does not regulate the amount and requirements for mandatory bequests for heirs of different religions. The problem studied in this research is how the mandatory Testaments of heirs of different religions are regulated according to Islamic law and is related to the basis for considering the judge's decision regarding the mandatory Testament of heirs of different religions. This research is Normative Law research using legal literature with a statutory regulation approach, case approach and conceptual approach. The result of this research is that the Compilation of Islamic Law does not regulate the size of the share and requirements for obligatory Testament for heirs of different religions, but only for heirs who do not get their rights because they are hindered by sharia, such as adopted children and adoptive parents. Judges have the authority to carry out rechtvinding or ijtihad in resolving cases if a legal vacuum occurs. This is reflected in several Court decisions and Constitutional Court decisions which provide mandatory Testament for heirs of different religions based on considerations of humanity and justice